Video Blog Sebagai Media Kampanye Program Generasi Berencana dalam Pencegahan Stunting - Prita Suci Nurcandrani; Wiwi Susanti; Hanugrah Banyu Narmada (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2022)
The total number of Baduta 0-23 months of age in the working area of the Puskesmas Purwokerto Utara II was 593 children, and as many as 58 or 9.78 percent of them experienced stunting. The Puskesmas tries to implement health promotion that focuses on the GenRe program which primarily targets youth. The Service Team succeeded in creating a video blog campaign media to help intervene in the needs of the Puskesmas socialized to adolescents with the aim of being able to disseminate information and education about the dangers of stunting and its prevention. The vlog with a duration of 04.50 minutes is entitled "The Role of Quality Youth: Realizing a Stunting-Free Healthy Indonesia" and adapted to the "GenRe; The Young Who Plans". This video has been disseminating to adolescents in the working area of the Puskesmas and will continue to evaluate its effectiveness.